2018
DOI: 10.1016/j.stem.2018.04.001
|View full text |Cite
|
Sign up to set email alerts
|

Fasting Activates Fatty Acid Oxidation to Enhance Intestinal Stem Cell Function during Homeostasis and Aging

Abstract: Diet has a profound effect on tissue regeneration in diverse organisms, and low caloric states such as intermittent fasting have beneficial effects on organismal health and age-associated loss of tissue function. The role of adult stem and progenitor cells in responding to short-term fasting and whether such responses improve regeneration are not well studied. Here we show that a 24 hr fast augments intestinal stem cell (ISC) function in young and aged mice by inducing a fatty acid oxidation (FAO) program and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
312
2
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 293 publications
(361 citation statements)
references
References 59 publications
15
312
2
1
Order By: Relevance
“…Both led to an increase in ISC number and function (Beyaz et al, 2016;Mihaylova et al, 2018). However, while fasting improved ISC function during aging and regeneration (Mihaylova et al, 2018), HFD enhanced the capacity of ISCs to promote tumors upon loss of Apc (Beyaz et al, 2016). A recent study confirmed that FAO is required for ISC maintenance under normal conditions in mice .…”
Section: Fatty Acid Oxidationmentioning
confidence: 99%
See 1 more Smart Citation
“…Both led to an increase in ISC number and function (Beyaz et al, 2016;Mihaylova et al, 2018). However, while fasting improved ISC function during aging and regeneration (Mihaylova et al, 2018), HFD enhanced the capacity of ISCs to promote tumors upon loss of Apc (Beyaz et al, 2016). A recent study confirmed that FAO is required for ISC maintenance under normal conditions in mice .…”
Section: Fatty Acid Oxidationmentioning
confidence: 99%
“…In mammals, both a high fat diet (HFD) and fasting regimens have been shown to promote FAO through PPARδ, and CPT1A in the case of fasting. Both led to an increase in ISC number and function (Beyaz et al, 2016;Mihaylova et al, 2018). However, while fasting improved ISC function during aging and regeneration (Mihaylova et al, 2018), HFD enhanced the capacity of ISCs to promote tumors upon loss of Apc (Beyaz et al, 2016).…”
Section: Fatty Acid Oxidationmentioning
confidence: 99%
“…Moreover, FMD cycles ameliorate or reverse disease progression in mouse models of multiple sclerosis (MS), and type I, and type II diabetes (Choi et al, 2016; Cheng et al, 2017). Recent studies also showed positive effects of a 24-hour fast on intestinal stem cell function in young and aged mice by a fatty acid oxidation pathway (Mihaylova et al, 2018). …”
Section: Introductionmentioning
confidence: 99%
“…Co., Ltd. Inc.). The sequences of Pck1 and Cpt1a primers were referred to a previous report 44,45 . The relative amounts of these mRNAs were normalized using the Actb mRNA signal.…”
Section: Gut Microbiome Analysis Of Japanese Long-distance Runnersmentioning
confidence: 99%
“…During exercise, subjects maintained a pedal speed of 60 rpm. RPE was measured with the Borg scale at baseline and at 10,20,30,40,45, and 50 min of exercise. In addition, a VAS questionnaire was used to assess fatigue after exercise testing (0, 30, 60 min).…”
Section: Human Study With Flaxseed Lignan or α-Cyclodextrin As Test Fmentioning
confidence: 99%